A fei zheng zhuan = Days of being wild [videorecording (DVD)] - Wong, Kar-wai, 1958-; Wong, Kar-wai, 1958-; Tang, Rover; Cheung, Leslie, 1956-2003; Zhang, Manyu; Lau, Andy, 1961-; Liu, Jialing, 1964-; Zhang, Xueyou (Wong Kar-wai Collection., 2004)
Set in 1960s Hong Kong, this is the story of six young people whose lives intersect in passionate love-hate relationships. The film centers on the young and handsome Yuddy, who learns from the drunken ex-prostitute who raised him that she is not his real mother.